Shakespeare on the couch on behalf of the United Kingdom Council for Psychotherapy / by Michael Jacobs. - Jacobs, Michael, 1941- (UKCP., 2008)
Drawing upon a vast literature in psychoanalytic journals and either upon Shakespeare's characters themselves or alluding to those characters in the course of other topics, this book discusses eight of Shakespeare's plays and the relationships between the main characters in them.